Case study of an integrated system for olive mill by-products management in Sfax region in central Tunisia - Gargouri K.; Ben Rouina B.; Rhouma A.; Ayadi M.; Abichou M.; Bentaher H. (Present and future of the Mediterranean olive sector, 2013)
Olive oil extraction generates annually a huge amount of by-products called olive mill wastewater (OMW) and olive husk in the whole of the producing countries all around the Mediterranean basin. In the particular situation of Sfax (a city in the Center of Tunisia) the major part of the 400 olive mills is located in the urban area. This situation makes olive mil by-products disposal and management hard. This work focused on the agronomical valorisation of these by-products. OMW was directly spread in fields while olive husk was primarily composted with cow manure. The technical and agronomic efficacy of these valorization ways was confirmed through three years field studies. Indeed, OMW spread improved soil cation exchange capacity as well as soil fertility with regards to organic and mineral compounds. The obtained olive husk compost was an organic fertilizer of high quality. The agronomic valorisation of olive mill by-products was technically realisable with important beneficial effects on soil and plants and with very limited impacts on environment. The cost of these techniques is moderate and comparable to the cost of actual disposal methods. This makes the integrated way of management interesting and practically feasible at wide scale. This method involve olive mill by-products transport, temporary storage or composting and spread in the fields.
International Seminar: Present and Future of the Mediterranean Olive Sector, 2012/11/26-28, Zaragoza (Spain)